PENGARUH MEDIA SOSIAL DAN EFIKASI DIRI TERHADAP PERILAKU KONSUMTIF SISWA SMA NEGERI 8 PADANG - Artati Anggita Putri; Reni Respita; Widya Astuti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2024)
This study aims to determine the influence of social media and self-efficacy on the consumer behavior of students at SMA Negeri 8 padanng. The population is 233 and the sample is 147 students. The type of quantitative research is with questionnaire and literature. The results of the social media research have a t-count of 4.726 > t-table of 1,97658 and a significant value of 0.000 < 0.05. This means that H1 is accepted. So it can be concluded that social media does not have a significant effect on the consumer behavior of SMA Negeri 8 Padang students. Self-efficacy has a t-count of 3.212 > t-table of 1,97658 and a significant value of 0.000 < 0.05. This means that H2 is accepted. So it can be concluded that self-efficacy has a significant effect on the consumer behavior of SMA Negeri 8 Padang students and social mediaand efficacyhas a calculated F value of 20.745 > 3.06 and asignificant value of 0.000 <0.05. This means that H3 is accepted. So it can be concluded that social media and self-efficacy together have a significant effect on the consumer behavior of SMA Negeri 8 Padang students.